Rehabilitating a brain with Alzheimer's: a proposal - Gonzalo Emiliano Aranda-Abreu (Dove Medical Press, 2011)
Gonzalo Emiliano Aranda-Abreu1,3, María Elena Hernández-Aguilar1,3, Jorge Manzo Denes1,4, Luis Isauro García Hernández1,4, Marisol Herrera Rivero21Programa de Neurobiología, 2Doctorado en Ciencias Biomédicas, Universidad Veracruzana, Xalapa, Veracruz, México, 3Cuerpo Académico de Neuroquímica, 4Cuerpo Académico de Neurociencias.Abstract: Alzheimer's disease (AD) is the most common neurodegenerative disorder, originating sporadically in the population aged over 65 years, and advanced age is the principal risk factor leading to AD development. In spite of the large amount of research going on around the globe and all the information now available about AD, there is still no origin or triggering process known so far. Drugs approved for the treatment of AD include tacrine, donepezil, rivastigmine, galantamine, and memantine. These may delay or slow down the degenerative process for a while, but they can neither stop nor reverse its progression. Because that this might be due to a lack of effect of these drugs on degenerating neurons, even when they are able to potentiate the brain in nondegenerative conditions, we propose here an alternative therapy consisting of initial repair of neuronal membranes followed by conventional drug therapies. The rehabilitation of neurons in a degeneration process would enable the drugs to act more effectively on them and improve the effects of treatment in AD patients.Keywords: Alzheimer, Rehabilitation, Drugs